Evaluating Students' Technology Acceptance of Use of Metaverse as an Educational Information System for Hybrid Education - Classe, Tadeu Moreira de; Castro, Ronney Moreira de; Sousa, Henrique Prado De Sá (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2023)
Context: COVID-19 has brought new challenges and chances to modern society. During that time, Information Systems (IS) become more indispensable to people's lives. Especially in the educational field, new technologies and ISs, such as metaverses, arose as innovations for remote and blended education. Problem: However, there needs to be more research on using metaverses as educational ISs applied to the hybrid context. Solution: In this study, we explored a metaverse as an educational IS in a real context for an undergraduate IS course. Method: As a research method, we used a quasi-experimental, aiming to evaluate students’ perceptions and acceptance of using the metaverse as IS to support blended education. IS Theory: All the evaluation was designed based on the Technology Acceptance Model (TAM). Summary of Results: We analyzed data through a quantitative approach, using descriptive and inferential statistics. As a result, we observed evidence of the acceptance of metaverse as educational IS in the blended context. It was considered easy and useful by students. Contributions to IS: Therefore, we proposed new technologies being applied as IS for educational contexts. With our research, we have been covering a need for studies about metaverses for blended purposes. Thus, we glimpse reflections and opportunities to use those metaverse systems in other themes in which the blended context could be advantageous.